Análise de aminas aromáticas em amostras de interesse ambiental por cromatografia líquida de alta eficiência acoplada a detectores de arranjo de diodo, eletroquímico e espectrometria de massas: Thiago Mescoloto Lizier. - - Lizier,Thiago Mescoloto [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This work investigates new analytical methods for analysis of aromatic amines selected because of their toxicological and/or mutagenic properties in samples of environmental interest using chromatographic techniques with various detectors. After optimization of chromatographic conditions as aromatic amines: 4,4'-oxydianiline, aniline, 2,4-diaminotoluidina, 4,4'- diaminobifenila, 4,4'-methylenebis-(2-chloroaniline), 3,3'-dichlorobenzidine, 2- aminonaphthalene, 2-methylaniline, 2-methoxyaniline, 4,4'-diaminodiphenylmethame, 2-chloro- 4-nitroaniline, 4-aminobifenila, 2-methoxy-5-methylaniline, 3,3'-dimethoxybenzidine, 4- chloroaniline and 3,3'-dichlorobenzidine showed well defined peaks in the mobile phase methanol/water 70:30 (v/v) and a flow rate of 0.8 mL min-1 classified as group I. The amines 1,4- diaminobenzene, 4,4'-methylbenzene-1,4-diamine, p-aminophenol, N-monoacethyl-1,4- diaminobenzene, 2,5-dimethylaniline, 4,4'-methylene-bis-2-methylaniline and 4-chloro-2- methylaniline were grouped in group II, best separated in the mobile phase acetonitrile/water 60:40 (v/v), flow rate 0.8 mL min-1 and T = 40°C. The comparison between the diode array detector (DAD) and electrochemical (ED) were conducted on these optimized conditions, linear calibration curves were constructed for all these amines from 1 to 250 mg L-1 (DAD detector = 230 nm) and 0.5 to 250 mg L-1 (detector ED - Ep = +1.0 V), using for this purpose the addition of 30 x 10-3 mol L-1 of BMIm-NTf2 ionic liquid (1-butyl-3-methylimidazolium-bis- (trifluoromethylsulfonyl)imide). The addition of ionic liquid promoted better separation and increase in the intensity of the chromatographic peaks in both detectors. The HPLC-DAD and HPLC-ED detection limit of the amines showed values between 1.27 to 10.2 mg L-1 and 1.33 to 6.04 mg L-1, respectively. The HPLC-DAD and HPLC-ED limit of quantification of the amines showed values between 4.24 to 34.0 mg L-1 and from 4.44 to 20.1 mg L-1,...

O presente trabalho investiga novos métodos analíticos para análise de aminas aromáticas selecionadas em virtude de suas proprideades toxicológicas e/ou mutagênicas em amostras de interesse ambiental usando técnicas cromatográficas com diversos detectores. Após otimização das condições cromatográficas as aminas aromáticas: 4,4'-oxidianilina, anilina, 2,4- diaminotoluidina, 4,4'-diaminobifenila, 4,4'-metileno-bis-(2-cloroanilina), 3,3'-diclorobenzidina, 2- aminonaftaleno, 2-metilanilina, 2-metoxianilina, 4,4'-diaminodifenilmetano, 2-cloro-4-nitroanilina, 4-aminobifenila, 2-metoxi-5-metilanilina, 3,3'-dimetoxibenzidina, 4-cloroanilina e 3,3'- diclorobenzidina apresentaram picos bem DEfinidos em fase móvel metanol/água 70:30 (v/v) e vazão de 0,8 ml min-1 classificadas como grupo I. As aminas 1,4-diaminobenzeno, 4,4'- metilbenzeno-1,4-diamina, p-aminofenol, N-monoacetil-1,4-diaminobenzeno, 2,5-dimetilanilina, 4,4'-metileno-bis-2-metilanilina e 4-cloro-2-metilanilina foram agrupadas no grupo II, melhor separadas em fase móvel acetonitrila/água 60:40 (v/v), vazão 0,8 ml min-1 e T= 40 C. A comparação entre os detectores de arranjo de diodos (DAD) e eletroquímico (ED) foram conduzidos nestas condições otimizadas e curvas analíticas lineares foram construídas para todas estas aminas entre 1 a 250 mg L-1 (detector DAD = 230 nm) e 0,5 a 250 mg L-1 (detector ED - Ep = +1,0V)), utilizando para isto a adição de 30 x 10-3 Mol L-1 do líquido iônico BMIm-NTf2 (1-butil-3-metilimidazólio de bis(trifluorometilsulfonil)imida). A adição do líquido iônico promoveu melhor separação e aumento na intensidade dos picos cromatográficos em ambos os detectores. O limite de detecção das aminas por HPLC-DAD e HPLC-ED mostraram valores entre 1,27 a 10,2 mg L-1 e 1,33 a 6,04 mg L-1, respectivamente. O limite de quantificação das aminas por HPLC-DAD e HPLC-ED mostraram valores entre 4,24 a 34,0 mg L-1 e 4,44 a 20,1 mg L-1, ...
Keywords: Quimica analitica; Aminas; Agua potavel; Amines